Solar Distillation with Nanoparticle Integrated PCM - Prof. Prathmesh Chinta, Pallavi Bhosale, Sayali Bhabal,Gaurav Dethe, Dr. Madan Jagtap (International Journal of Advanced Science and Technology, 2020)
The test examination has been done in the period of April, 2019 for the climatic states of Koparkhairane, Navi Mumbai, Maharashtra, India with latitude 19.1028°N and longitude 73.0090°E. The reason behind this undertaking is to explore the impact of Nano-Composite material on the activity of a conventional sun solar still. The sunlight based still utilized in this examination is of single slope type because of its simplicity of creation and cost amicability. In this venture the customary sun based refining process which is improved by the utilization of nanoparticle incorporated Phase Change Material as inert warmth stockpiling medium. For the experimentation, CuO nanoparticles of 10nm size are implanted in Paraffin Wax as Phase Change Material by ultra-sonication process for even scattering of nanoparticles. Paraffin Wax can discharge its inactive warmth amid stage change process which improved not just the time term of the refining procedure yet in addition the efficiency and productivity on every hour premise. Timeframe of experimentation was of 12hours (from 8am to 8pm). In spite of the fact that a further water quality examination should be examine , the investigation uncovers promising outcomes for cutting edge sun powered refining process.